1974
DOI: 10.1017/s0003356100022819
|View full text |Cite
|
Sign up to set email alerts
|

A note on the effect of bovine somatotrophic hormone on wool production in growing lambs

Abstract: SUMMARYIn two experiments carried out on 36 crossbred growing lambs the effect of purified bovine somatotrophic hormone (STH) on wool production and some qualitative fleece characters was studied. Food intake during and after the hormonal treatment was also examined. STH, injected in a dose of 1 mg/kg of body weight in 10- or 15-day intervals to growing lambs from 2 to 100 days of age, increased fleece weight significantly. This increase was accompanied by considerably higher daily food intake both during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1
1

Year Published

1985
1985
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 3 publications
0
5
1
1
Order By: Relevance
“…Wool growth w".s significantly stimulated by daily GH injections (0·1 mg kg-1 liveweight) for a period of 12 weeks; this response was decreased by the simultaneous administration of bromocryptine. In contrast to the report of Reklewska (1974), these results could not be explained by an increase in feed intake in the GH-treated animals, although greater efficiency of feed conversion in GH-treated animals may in part account for the improved wool growth. The present results were derived from mature animals provided with a defined energy intake for an extended period to ensure stability of wool growth.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Wool growth w".s significantly stimulated by daily GH injections (0·1 mg kg-1 liveweight) for a period of 12 weeks; this response was decreased by the simultaneous administration of bromocryptine. In contrast to the report of Reklewska (1974), these results could not be explained by an increase in feed intake in the GH-treated animals, although greater efficiency of feed conversion in GH-treated animals may in part account for the improved wool growth. The present results were derived from mature animals provided with a defined energy intake for an extended period to ensure stability of wool growth.…”
Section: Discussioncontrasting
confidence: 99%
“…Significant increases in clean wool weight in response to bovine GH injections (1 mg kg-1 every 10 or 15 days until weaning at 100 days) have been measured in growing lambs by Reklewska (1974), although this response may be explained by an increase in feed intake in the GH-treated animals. Nevertheless, the observation that feed intake remained stimulated for 15 weeks posttreatment suggested that GH had a persistent metabolic effect long after circulating GH concentrations had returned to basal levels, an effect which is consistent with the wool growth responses in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…report a positive effect of somatotropin on growth in sheep. Subsequently, a number of studies reported similar effects (Wolfrom, Ivy and Baldwin, 1985;Heird, Hallford, Spoon, Holcombe, Pope, Olivares and Herring, 1988;Zainur, Tassell, Kellaway and Dodemaide, 1989) while others showed no effects of somatotropin on growth (Reklewska, 1974;Muir, Wien, Duquette, Ricks and Cordes, 1983).…”
Section: Introductionmentioning
confidence: 86%
“…Of the studies which have shown a significant effect, some observed an increase during the treatment period (Ferguson, 1954;Johnsson, Hart and Butler-Hogg, 1985;Johnsson, Ha thorn, Wilde, Treacher and ButlerHogg, 1987), some a decrease during treatment (Wheatley, Wallace and Bassett, 1966;Wynn, Wallace, Kirby and Annison, 1988) and others an increase after cessation of somatotropin treatment (Ferguson, 1954;Wheatley et al, 1966;Reklewska, 1974;Wynn et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Cependant, les premières expérimentations consacrées à l'étude des effets de la GH exogène sur la croissance se sont souvent soldées par des échecs chez le porc, le mouton et le bovin (Turman et Andrews, 1955 ;Henricson et Ullberg, 1960 ;Wheatley, 1966 ;Vézinhet, 1973 ;Reklewska, 1974 ;Muir et al, 1983 ;Brumby, 1959 ;Znidar, 1976 (Adam et al, 1985). Un bref résumé est repris ci-dessous.…”
Section: Introductionunclassified